Communication for sustainable development - Balaswamy , B. (New Delhi, 2006)
This book is an outcome of research work, which has both theoretical as well as empirical components. It seeks to explore the implications of sustainable development for communication; analyze the role of communication in sustainable development and describe the policies and programmes of Indian government towards sustainable development. Research indicates that communication is pivotal to achieving the goals of sustainable development. This study carried out in a backward and environmentally affected district reveals that various communication channels including mass media played a significant role in strengthening the environmental movement. The awareness among people about various environmental issues is influenced by the first hand experience, education and exposure to mass media. The study further reveals that communication is one of the determining elements in the successful utilization of poverty alleviation schemes. This book will be useful for the scholars and students of Mass Media, Developmental Communication and Rural Development and also for the planners and policy makers
Keywords: Sustainable development-India